(untitled) (Research, Society and Development, 2020)
In order to estimate the costs of mining enterprises correctly before the construction of the mining it is important to determine the viability of the mineral deposit. There is no standardization of the methods of estimating operating costs of these projects. Regression-based equations are used to forecast costs and, as a result, differences arise between the results. This study analyses different estimation models with a focus on capital costs, that is, those associated with the necessary infrastructure for opening an open pit mine - mining and processing. Two methodologies were evaluated in order to determine which is more assertive. Monte Carlo simulations were performed to check the compatibility between the methods based on the limits of the analysed models. The study was able to determine which model underestimates costs, with the risk of pointing out the economic viability of projects that are not viable in light of the real cost.